PENGARUH ETIKA KERJA TERHADAP KETERLIBATAN KERJA DAN IMPLIKASINYA TERHADAP KOMITMEN KERJA, KEPUASAN KERJA DAN KINERJA PEKERJAAN PADA KARYAWAN LEMBAGA PENDIDIKAN TINGGI - Tery Aris Archandar (Jurnal Manajemen dan Pemasaran Jasa, 2010)
Employees as human resources can do or can not do all the activities efficiently and effectively for the organization or company to face private higher education competition and realize the educational mission of the Trisakti University, “Being a leading university, international quality in developing science, technology and improve the quality of life and civilization”. Thepurpose of the study was to determine the effect of the relationship between work ethic to work involvement and its implications for commitment and job satisfaction and job performance at Trisakti University employees. The number of respondents who obtained as many as 194 employees.With the analysis of the data used is descriptive analysis and Structural Equation Modeling, (SEM) using the statistical program LISREL 8.7 for Windows.The research proves that: (a) the work ethic has a significant impact on work involvement; (b) only work involvement has a significant contribution to affective commitment and the commitment continuum, including a significantfunction as a mediating variable between ethics and affective commitment and continuous commitment; (c) the involvement of work has contributed significantly to job satisfaction; (d) the continuous commitment and career commitment has a significant contribution to job satisfactionas well as the two variables have a function as a mediating variable ; (e). job satisfaction has a significant contribution to job performance and has a function as a mediating variable between commitments with job performanceKeywords : Work commitments, work ethics, work involvement, job satisfaction, and job performance.